Analysis of the Values ​​of Faith Education in the film Ayat-Ayat Cinta 2: Analisis Nilai-Nilai Pendidikan Akidah dalam Film Ayat-Ayat Cinta 2 - Rachma, Nadya; Astutik, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2022)
This type of research is library research with case study method. The research subject used is the film Ayat-Ayat Cinta 2. The data collection technique used is documentation that looks for data about things or variables in the form of transcripts, newspapers, books, magazines, and so on. In this thesis, observations are made on the film Ayat Ayat Cinta 2, notes and evidence on VCDs and books related to the research.Based on the research conducted, there are several results of his research, there are 18 scenes that contain the value of faith, for example such as the importance of peace, the obligation to pray, being honest, friendly to others, always helping others, meeting prayer tables are sunnah, being proud and accepting mistakes. what has been done, sincerity in helping is the key to a blessing, kindness will give birth to other goodness.